Tolerability of Breast Radiotherapy Among Carriers ofATMGermline Variants. (December 2021) - Modlin, Leslie A.; Flynn, Jessica; Zhang, Zhigang; Cahlon, Oren; Mueller, Boris; Khan, Atif J.; Gillespie, Erin F.; McCormick, Beryl; Stadler, Zsofia K.; Robson, Mark E.; Powell, Simon N.; Braunstein, Lior Z.
Abstract : PURPOSE : ATM, a gene that controls repair of DNA double‐strand breaks, confers an excess lifetime risk of breast cancer among carriers of germline pathogenic variants (PV). ATM PV homozygotes are particularly sensitive to DNA damage caused by ionizing radiation. Consequently, there is concern that adjuvant radiotherapy (RT) may cause excess morbidity among heterozygous carriers of ATM PV. We evaluated the tolerability of breast RT among carriers of ATM germline variants. METHODS : Of 167 patients with ATM germline variants presenting to our institution with breast cancer, 91 received RT. Treatment‐related toxicity was ascertained from medical records and graded across organ systems. Toxicities grade ≥ 2 were recorded from the end of treatment to last evaluable follow‐up and were analyzed according to ATM variant pathogenicity. RESULTS : Of 91 evaluable carriers of ATM variants, with a median follow‐up of 32 months following RT, 25% (n = 23) harbored a PV, whereas 75% (n = 68) harbored a variant of uncertain significance (VUS). Prevalence of grade ≥ 2 toxicity unrelated to post‐mastectomy reconstruction among patients with ATM PV was: 32% at the end of treatment ( v 34% for VUS carriers), 11% at 1 year of follow‐up ( v 4% for VUS carriers), and 8% at the last follow‐up ( v 13% for VUS carriers), consistent with previous studies of RT among unselected populations. No grade 4 or 5 toxicities were observed. ATM variant pathogenicity was not associated with local toxicity, contralateral breast cancer, or secondary malignancy in this limited cohort of patients who received breast RT. CONCLUSION : We found no evidence of excess RT‐associated toxicity among carriers of pathogenic ATM germline variants. Breast‐conserving therapy and adjuvant RT may be safely considered among appropriately selected carriers of ATM germline variants.